Exploring The Nexus Among Green Supply Chain Management, Environmental Management, And Sustainable Performance: The Mediating Role Of Environmental Management - MARRI, MUHAMMAD YOUSUF KHAN; SARWAT, NOSHEEN; AQDAS, RAMAISA; NADEEM, SHAHID (The journal of contemporary issues in business and government, 2021)
The main objective of the current study is to investigate the direct relationship between the green supply chain management, environmental management, and sustainable performance. In addition to that the study has also examined the mediating role of environmental management. The manufacturing firms listed in PSX are chosen as a sample of the study. The study has employed the survey based methodology and the data were collected with the aid of a questionnaire. The response rate after omitting unusable questionnaires is 59.6%. For the data analysis, the study has chosen, SEM-PLS, which is one of the most robust technique for the data analysis. The findings of the study have shown agreement with the hypothesized results. The response rate after omitting unusable questionnaires is 59.6%. The researchers highlighted the presence of two different mediation impacts between the internal and external GSCM activities or both are the mediators of these associations. The scholars highlighted the presence of two different mediation impacts between internal and external GSCM practices and organizational economic performance enhancement. The study will be helpful for practioners, and policymakers in understanding the issues related to green supply chain management, environmental management, and sustainable performance.